2023
DOI: 10.1002/ila2.25
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Torsin‐1A‐interacting protein 1 as a predictive and immunological biomarker in cancer

Gurleen Kaur,
Gurparsad Singh Suri,
Dheeraj Shinde

Abstract: BackgroundCancer poses a significant global challenge, and with the projected rise in cancer incidence, there is an urgent need to discover new targets and treatments to improve patient outcomes. Recent advancements in genomics technologies have enhanced our understanding of cancer's complexities and led to the emergence of pan‐cancer analysis as a valuable approach for identifying tumor targets. Torsin‐1A‐interacting protein 1 (TOR1AIP1) is a membrane protein involved in various cellular processes. Emerging e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 45 publications
0
0
0
Order By: Relevance
“…Of note, this association of loss-of-function TOR1AIP1 mutations with the development of nuclear envelopathies [ 13 , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] ], allied to the fact that Tor1aip1 −/− mice display perinatal lethality [ 25 ], is another indicator of the paramount importance of LAP1 for normal cellular functioning. Moreover, it has recently been found that TOR1AIP1 expression is significantly altered in various tumor types [ 26 ] and that LAP1 upregulation can contribute to an enhanced migratory and invasive ability of melanoma cells [ 27 ], which indicates that LAP1 may also be involved in cancer. Altogether, there is considerable evidence pointing to the necessity of deciphering human LAP1 (dys)function.…”
Section: Introductionmentioning
confidence: 99%
“…Of note, this association of loss-of-function TOR1AIP1 mutations with the development of nuclear envelopathies [ 13 , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] ], allied to the fact that Tor1aip1 −/− mice display perinatal lethality [ 25 ], is another indicator of the paramount importance of LAP1 for normal cellular functioning. Moreover, it has recently been found that TOR1AIP1 expression is significantly altered in various tumor types [ 26 ] and that LAP1 upregulation can contribute to an enhanced migratory and invasive ability of melanoma cells [ 27 ], which indicates that LAP1 may also be involved in cancer. Altogether, there is considerable evidence pointing to the necessity of deciphering human LAP1 (dys)function.…”
Section: Introductionmentioning
confidence: 99%